Beazley Designs of the Year 2018 - Chen, Aric; Watson, Eleanor (Design Museum Publishing, 2018)
Now in its eleventh year, the Design Museum's Beazley Designs of the Year award and exhibition showcase the most innovative, relevant and thought-provoking projects in contemporary design. 0From the first iPhone to Zaha Hadid's final building, the nominations for the award have spanned the fields of architecture, digital, fashion, graphics, product and transport. Introduced by Deyan Sudjic and guest curator Aric Chen of M+ in Hong Kong, this illustrated book brings together all the nominated designs for 2018, along with the reasons for their selection by an international group of design experts, practitioners and critics, including Iwan Baan and Hans Ulrich Obrist. It is a snapshot of the most exciting things happening in design today. Exhibition: Design Museum, London, UK (12.09.2018-06.01.2019)
Umschlagtitel. - Acknowledgements: This catalogue was published in conjunction with the exhibition "Beazley Designs of the Year 2018" at the Design Museum, 12 September 2018 to 6 January 2019
Keywords: Geschichte 2018; Kunstpreis; Design; Ausstellungskatalog -- Design Museum -- 12.09.2018-06.01.2019 -- London; Bildband